Aggressiveness of Puccinia striiformis f. sp. tritici Isolates at High Temperatures: A Study Case in Core Oversummering Area of Gansu as Inoculum Source - Bo Zhang; Jie Zhao; Jin Huang; Xiaojie Wang; Zhijie Guo; Qiuzhen Jia; Shiqin Cao; Zhenyu Sun; Huisheng Luo; Zhensheng Kang; Shelin Jin (Plants)
Wheat stripe rust, caused by a biotrophic, obligate fungus Puccinia striiformis f. sp. tritici (Pst), is a destructive wheat fungal disease that exists worldwide and caused huge yield reductions during pandemic years. Low temperatures favor the development of the disease, but the global average temperature has been increasing since 1850, especially in China, which has a higher rising rate than the global average. In the last two decades, Pst isolates have shown increased aggressiveness under high temperatures. However, the effect of rising temperatures on the aggressiveness of Pst has remained unknown in China. Therefore, this study assessed the aggressiveness of 15 representative Pst isolates (6 new isolates collected before 2016 and 9 old isolates collected after 2016) in Gansu under high temperatures by measuring and comparing disease severity, spore germination, and latent period on wheat seedlings at 16 °C, 18 °C, and 22 °C. The results indicated that the six new isolates showed greater disease severity, higher spore germination ratio, and shorter latent period than the nine old isolates, indicating that the new isolates were more aggressive under high temperatures than the old isolates. Some new isolates, such as CYR34, CYR33, and CYR32, which are predominant, were inferred to be associated with high-temperature adaptation in addition to having more susceptible hosts. Our results provided an insight into changes in Pst isolates at warmer temperatures and increasing incidence of wheat stripe rust in China, especially in eastern sporadic epidemiological areas in recent years. Thus, the new isolates are likely to be a potential risk for causing increasing stripe rust incidence.